Effect of boundary conditions on energy harvesting of a flow-induced snapping sheet at low Reynolds number - Wang, Zhaokun (2024)
Recent studies on the snap-through motion of elastic sheets have attracted intense interest in energy-harvesting applications. However, the effect of boundary conditions (BCs) on energy extraction performance still remains an open question. In this study, we explored the snapping dynamics and energy-harvesting characteristics of the buckled sheet at various conditions using fluid-structure interaction simulations at a Reynolds number Re = 100. It was found that the front boundary condition (BC) dramatically affects the sheet's snapping dynamics, e.g., the pinned or relatively soft front BC triggers the sheet's instability easily and thus boasts the collection of potential energy. In the snap-through oscillation state, a stiffer rear BC results in a larger improvement in the sheet's energy collection compared with a minor effect of front BC. Meanwhile, the enhancement can also be achieved by adjusting the rear rotational spring stiffness up to 1.125 × 10−4, after which it remains nearly constant, as observed in the case of EI* = 0.004. This introduction of an elastic BC with k r s * = 1.125 × 10−4 not only efficiently enhances energy extraction but significantly reduces stress concentration and, as a result, greatly prolongs the sheet's fatigue durability, especially for the stiffer sheet with EI* = 0.004. The effect of three other governing parameters, including the length ratio ΔL*, sheet's bending stiffness EI*, and mass ratio m*, on the sheet's energy-harvesting performance were also explored. The result shows that increasing ΔL* and EI* could improve the total energy harvested, primarily by enhancing the elastic potential energy, particularly in the aft half of the sheet. In contrast, increasing m* mainly enhances the kinetic energy collected by the sheet's central portion, thus improving the total energy-extracting performance. This study provides an in-depth insight into the dynamics of a buckled sheet under various BCs, which may offer some guidance on the optimization of relevant energy harvesters.